2000
DOI: 10.1148/radiology.215.1.r00ap4051
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Nonenhanced Helical CT of Renal Colic: Assessment of Ureteric Stone Detection and Measurement of Effective Dose Equivalent

Abstract: Our low-dose CT protocol is superior to IVU and clinically adequate for diagnosis of renal colic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(92 citation statements)
references
References 16 publications
2
86
0
4
Order By: Relevance
“…Our study shows that less than 2% of CT studies for work-up of kidney stones in this national registry used 3 mSv or less, and nearly 80% of institutions contributed no reduced-dose CT studies. The clinical appropriateness of lower-dose techniques has been demonstrated for more than a decade now; however, our study shows that little progress has been made in the routine clinical application of these techniques in the United States (13). The reduction of dose associated with medical imaging is an important public health and patient safety priority (31), and efforts to use reduced-dose techniques must be strengthened to make meaningful improvements in patient safety.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our study shows that less than 2% of CT studies for work-up of kidney stones in this national registry used 3 mSv or less, and nearly 80% of institutions contributed no reduced-dose CT studies. The clinical appropriateness of lower-dose techniques has been demonstrated for more than a decade now; however, our study shows that little progress has been made in the routine clinical application of these techniques in the United States (13). The reduction of dose associated with medical imaging is an important public health and patient safety priority (31), and efforts to use reduced-dose techniques must be strengthened to make meaningful improvements in patient safety.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that reduced-dose CT studies are accurate for the detection of renal stones (13)(14)(15)(16)(17)(18)(19). A meta-analysis (20) of reduced-dose CT for renal colic (with effective dose less than 3 mSv) yielded a pooled sensitivity and specificity of 0.97 and 0.95, respectively, compared with conventional CT.…”
mentioning
confidence: 98%
“…Because the received dose is proportional to the square of the kilovoltage, use of this technique can lead to an approximately 40% increase in received dose, possibly less. The second acquisition thus can be minimal (centered on the stone without acquisition of images of the rest of the abdomen) and performed with low energy (80 kV) [38][39][40]. This additional dose can be a problem for children but can be justified for adult patients because accurate and fast determination of the chemical characterization of renal stones can lead to quicker and more accurate treatment.…”
Section: Grosjean Et Almentioning
confidence: 99%
“…As for pitch, an increase in pitch decreases duration of examination and also decreases radiation exposure to the body. Although increase of pitch causes helical artifacts and decreased spatial resolution, some investigators have reported using a pitch of 2 or above with satisfactory results in cases of suspected renal colic (20,21).…”
Section: Radiation Dose Optimization and Dose Reduction: Alara (As Lomentioning
confidence: 99%
“…X-ray filters decrease "soft X-rays" which never reach the detectors and thus do not contribute to the image. Studies have shown that using effective X-ray filters causes a reduction in the radiation exposure and decrease in noise at a very-low-dose CT (21,24). Automatic tube current modulation can be defined as a set of techniques that enable automatic adjustment of the tube current according to the size and attenuation characteristics of the body part being scanned and achieve constant CT image quality with lower radiation exposure (25).…”
Section: Radiation Dose Optimization and Dose Reduction: Alara (As Lomentioning
confidence: 99%